Systematic Literature Review Paradigma dalam Dunia Pendidikan - Ayatur Rahmi (Journal of Innovation in Teaching and Instructional Media, 2025)
The paradigm in the field of education continues to undergo significant changes in line with social, technological, and global needs. This article reviews various studies discussing the shift in educational paradigms, from the traditional one-way teaching paradigm to the constructivist paradigm and the integration of technology in learning. The reviewed research shows that this paradigm shift has a positive impact on improving the quality of education, emphasizing the active role of students in constructing knowledge through experience and collaboration. Furthermore, information and communication technology play a crucial role in enriching the learning experience, providing broader access, and creating more flexible and personalized learning environments. The concept of inclusive education is also becoming increasingly important to ensure that all students, including those with special needs, have equal opportunities to learn. This article aims to explore the evolution of educational paradigms and review journal articles from previous researchers.